Comparison Study of Light Curing System Penetration with Deferent Power for Multilabel Thickness and Types of Resin Disks. (Journal of Hama University, 2020)
Recently, different esthetic dental material had been used in fabricating dental prosthesis, like using photopolymer Resin via 3-D dental printer, and using PMMA blocks via Computer Aid Designed, Computer Aid Manufacturing CAD\CAM system, therefor, this study is conducted to evaluate the light curing penetration for these types of material for generating sufficient curing for the cement used to fixed these materials in comparing with direct risen composite.Different risen discs design using exocad software for each group of experimented material, photopolymer risen fabricated using 3D dental printing system, PMMA blocks fabricated using CAD\CAM system and the direct risen composite with three thickness (1-2-3) mm and different curing power.No statistical differences noted when using Mann-Whitney statistical test in comparing means curing numbers of the three group in the three thickness with two different light curing power in penetrating of sufficient curing light to generate complete curing for the cementing material with the two curing power except in CAD\CAM 1m group with the high power curing device (P=0.016 , P=0.048).The penetration of curing light was not enough to fully cur the cementing material used to fix the three experimented esthetic material in the three thickness with two different curing powers except in CAD\CAM 1mm with the high curing power